Theta burst stimulation in the rehabilitation of the upper limb: a semirandomized, placebo-controlled trial in chronic stroke patients. - Talelli, P; Wallace, A; Dileone, M; Hoad, D; Cheeran, B; Oliver, R; VandenBos, M; Hammerbeck, U; Barratt, K; Gillini, C; Musumeci, G; Boudrias, M; et al. (2012)
BACKGROUND: Noninvasive cortical stimulation could represent an add-on treatment to enhance motor recovery after stroke. However, its clinical value, including anticipated size and duration of the treatment effects, remains largely unknown. OBJECTIVE: The authors designed a small semi-randomized clinical trial to explore whether long-lasting clinically important gains can be achieved by adding theta burst stimulation (TBS), a form of repetitive transcranial magnetic stimulation (TMS), to a rehabilitation program for the hand. METHODS: A total of 41 chronic stroke patients received excitatory TBS to the ipsilesional hemisphere or inhibitory TBS to the contralesional hemisphere in 2 centers; each active group was compared with a group receiving sham TBS. TBS was followed by physical therapy for 10 working days. Patients and therapists were blinded to the type of TBS. Primary outcome measures (9-hole Peg Test [9HPT], Jebsen Taylor Test [JTT], and grip and pinch-grip dynamometry) were assessed 4, 30, and 90 days post treatment. The clinically important difference was defined as 10% of the maximum score. RESULTS: There were no differences between the active treatment and sham groups in any of the outcome measures. All patients achieved small sustainable improvements--9HPT, 5% of maximum (confidence interval [CI] = 3%-7%); JTT, 5.7% (CI = 3%-8%); and grip strength, 6% (CI = 2%-10%)--all below the defined clinically important level. CONCLUSIONS: Cortical stimulation did not augment the gains from a late rehabilitation program. The effect size anticipated by the authors was overestimated. These results can improve the design of future work on therapeutic uses of TMS.